What does 100% Compliance to the CIAT Open Access and Data Management Policy mean? - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2017)
CIAT aims to be 100% compliant to the CGIAR and CIAT Open Access and Data Management (OADM) policy by the end of 2017, one year ahead of the CGIAR stipulated goal. This short primer will briefly lay out requirements to ensure adherence to the OADM policy.